Satya - Navjeevan Singh (Research and Humanities in Medical Education, 2014)
Satya loved to tell his stories. As often happens, as he grew older, his own children grew weary of them. Being around more often than they were, I heard many; all but his last one. In retrospect I wish I had listened more carefully. Kept notes perhaps. You don’t realize the worth of these things until you no longer have them.